MUATAN MORAL DALAM CERITA NAGASASRA DAN SABUK INTEN KARYA S.H. MINTARDJA - Tri Handito; Kasiati Kasiati; Septi Septi (Universitas Muhammadiyah Surakarta, 2020)
This study aims to identify the content of moral values contained in the Nagasasra and Sabukinten stories written by SH Mintardja volumes I through volume III. This research is a content analysis research with a qualitative approach. In this research the researcher becomes the main instrument of data collection. In the process of collecting data, researchers used research aids in the form of data cards and check lists. Data cards were used to record sentences in the form of conversations and portrayals of the situation and behavior of characters in the Nagasasra and Sabuk Inten stories. The captured data was then presented in the form of a statement in the form of a description of moral values. The results of the study found that there were good moral values and bad moral values that are manifested in various depictions of the behavior of the characters. Good behavior includes godly values (in the form of belief in the existence and power of God, surrender/ surrender to God, giving thanks, repenting, praying, and praying), loyalty (in the form of loyalty between husband and wife, loyalty of a soldier towards the king / leadership, and loyalty to the land of his birth), love for the country, love for the environment, responsibility, honesty, being respectful and polite, humble, and the delivery of moral values in the form of song. The bad morals were reflected in bad behavior, including not believing in the existence and power of God, cruel, greedy, immorality, cunning / cheating, arrogant / proud, defaming, stealing / robbing, low self-esteem, despair, and destructive natural. The most moral values found in the Nagasasra and Sabuk Inten volumes I through III are the value of helping (31.15%), the value of courtesy (26.23%), the value of God (16.39%), the value of loyalty ( 9.84%), the value of responsibility (6.56%), the value of humility (4.92%), the value of love for nature (3.28%), and moral messages in the form of song (1.64%).